Pengaruh Hasil Dekomposisi Seresah Mahoni (Swietenia macrophylla King.) Terhadap Perkecambahan Biji, Infeksi M1koriza Vesikular-Arbuskular Dan Pertumbuhan Bibit Akasia (Acacia mangium Wild.) - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 1999)
ABSTRACT The aims of the study were to know the effects of phenolic compounds released from decomposed mahogany leaf litters on acacia seed germination, acacia seedling growth, root infection of vesiculararbuscular mycorrhizae ( VAM ), and phosphate absorption. The experiments were carried out using factorial completely randomized design, with four replicates. The first factor was the volume of mahogany litters, i.e.